(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
In the last decade, significant transformations in the clothing business have intensified competition, making consumer retention through increased repurchase intention a crucial strategy for building loyalty and encouraging positive recommendations. This study aims to analyze the influence of price, product quality, and service quality on repurchase intention at Toko Nyoman in Tabanan Regency. The research involved a population of 100 consumers selected using an accidental sampling method. Data collection was conducted through observation, interviews, and questionnaires measured on a five-point Likert scale. The analytical techniques employed include multiple linear regression analysis, determination tests, t-tests, and F-tests to examine the effects of price, product quality, and service quality variables on repurchase intention. The analysis results reveal that price, product quality, and service quality have a positive and significant influence on repurchase intention, both partially and simultaneously. Based on the findings, it is recommended that Toko Nyoman continuously improve product and service quality while implementing competitive pricing strategies to enhance customer repurchase intention. For future researchers, it is suggested to include other relevant variables and expand the research area to achieve more comprehensive results.